TEACHING METHODS OF THE SUBJECT TECHNOLOGY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The article discusses the issues of technology teaching methods, methods and teaching aids, which are developed by general didactics, general theory of learning and a number of tasks of this course.